Future Perspectives and Conclusions from Animal Models of CHI3L1-Related Inflammation-Associated Cancer - Emiko Mizoguchi; Siyuan Wang (Cells)
Among the molecules implicated in inflammation-associated tumorigenesis, Chitinase 3-like 1 (CHI3L1/YKL-40/Brp-39) has emerged as a particularly compelling target due to its multifaced roles in immune regulation, tissue remodeling, and cancer progression. Elevated CHI3L1 expression is observed in various human cancers and corresponding animal models. CHI3L1 directly promotes tumor cell proliferation and angiogenesis and also contributes to immune evasion by establishing an immunosuppressive environment in inflamed tissues. Mechanistically, CHI3L1 exerts its effects through the modulation of STAT3, MAPK, and PI3K/Akt signaling pathways and by interacting with cell surface receptors, such as IL-13Rα2 and RAGE. Studies using transgenic and knockout mouse models have revealed a strong association between CHI3L1 expression and cancer progression. In models of colon and lung cancer, CHI3L1 overexpression correlates with increased tumor size and number, whereas CHI3L1 deficiency markedly suppresses tumor formation. However, its involvement appears to be context-dependent and varies among different epithelial tumor types. These findings suggest that CHI3L1 is a potential therapeutic target and diagnostic biomarker for inflammation-associated cancers. Animal studies provide valuable insights into the immunological mechanisms of CHI3L1-mediated tumorigenesis but also highlight the need for cautious interpretation due to inherent technical limitations.